2014
DOI: 10.1063/1.4862217
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation of mouse brain using high-resolution anatomical models

Abstract: Transcranial magnetic stimulation (TMS) offers the possibility of non-invasive treatment of braindisorders in humans. Studies on animals can allow rapid progress of the research including exploring a variety of different treatment conditions. Numerical calculations using animalmodels are needed to help design suitable TMS coils for use in animal experiments, in particular, to estimate the electric field induced in animal brains. In this paper, we have implemented a high-resolution anatomical MRI-derived mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Decreasing coil size has raised the question of stimulation efficiency as smaller coils induce proportionally smaller electric fields. Our calculations are consistent with a model of a commercial TMS stimulator and coil over a mouse brain which found a peak magnetic and electric field of 1.7 T and 132 V/m respectively, approximately 1 order of magnitude larger than our small custom coils ( Crowther et al, 2014 ). Furthermore, our calculations suggest the induced electric field from the iron-core coil results in approximately 10% of the electric field needed for axonal suprathreshold stimulation (100 V/m).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Decreasing coil size has raised the question of stimulation efficiency as smaller coils induce proportionally smaller electric fields. Our calculations are consistent with a model of a commercial TMS stimulator and coil over a mouse brain which found a peak magnetic and electric field of 1.7 T and 132 V/m respectively, approximately 1 order of magnitude larger than our small custom coils ( Crowther et al, 2014 ). Furthermore, our calculations suggest the induced electric field from the iron-core coil results in approximately 10% of the electric field needed for axonal suprathreshold stimulation (100 V/m).…”
Section: Discussionsupporting
confidence: 86%
“…Dielectric properties for human gray matter and bone were used, and taken from the Foundation for Research on Information Technologies in Society dielectric tissue properties database ( Hasgall et al, 2014 ). These dielectric properties have been used in previous studies of magnetic stimulation in rodents ( Nowak et al, 2011 ; Gasca, 2013 ; Crowther et al, 2014 ), and are shown in Table 1 . Incorporating the frequency dependence of tissue is an important consideration, as low-frequency properties are controlled by the conduction of electrolytes in extracellular space, while high frequencies initiate several biophysical processes which change the dielectric properties of the tissue ( Foster, 2000 ).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, Biot Savart's law can be used to determine magnetic flux densities (commonly, h-fields) and induced electric fields (e-field), for a given coil with electric current produced from a pulse generator and a constant air permittivity. Most commonly, mathematical modeling of TMS is achieved through finite difference methods 15,16 .…”
Section: Mathematical Modeling Of Tmsmentioning
confidence: 99%
“…2) made of glass-ceramic that complements both the physiology of the mouse and the exact positioning of the coils needed to deliver a focused electric and magnetic field into the brain. The mouse considered here is OF1 type mouse whose typical dimensions are: total length of 95mm [16]; head length of 20mm and maximum head diameter of 12mm. The helmet features the ability to rotate, allowing for electric field profile adjustment within the brain, and foam near the mouse's head to secure the mouse position relative to the coils.…”
Section: Coil and Helmet Systemmentioning
confidence: 99%